Switzerland : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Switzerland. (IMF Staff Country Reports; Country Report ;, 2022)
Recovery was strong in 2021, but there are headwinds from the war in Ukraine. 2021 output was 1 percent higher than in 2019, but 2 percent below pre-Covid trends; unemployment is back to pre-crisis levels. Inflation has picked up (2.5 percent in April), but below other advanced economies. Strong exports/merchanting led to a higher current account surplus. Although the energy mix (nuclear, hydro) has limited exposure to Russia, exposures of commodity traders and indirect channels could be important. Growth is likely to slow to 2 1/4 percent in 2022 ( 3/4 ppt. drag from the war). Risks are to the downside (war escalation, Covid developments, real estate). Covid outlays are lower in 2022, but still large (1.2 percent of GDP). Outlays related to Ukraine are likely to be accommodated as extraordinary. The Swiss National Bank is closely monitoring inflation, seeing it returning to the 0-2 percent range this year. The authorities reactivated the sectoral CCyB for residential real estate. They are pursuing pension and labor reforms, climate initiatives, energy security, and renewed EU engagement.